Clinical Efficacy and Safety of Traditional Medicine Preparations Combined With Chemotherapy for Advanced Pancreatic Cancer: A Systematic Review and Meta-Analysis - Hu, Jiaqi; Jiang, Juling; Liu, Rui; Cheng, Mengqi; Zhu, Guanghui; He, Shulin; Shi, Bolun; Zhao, Yuwei; He, Zhongning; Yu, Huibo; Zhang, Xing; Zheng, Honggang; et al. (Frontiers in Oncology, 2022)
Background: Traditional medicine preparations (TMPs) combined with chemotherapy is widely used for patients with advanced pancreatic cancer (APC); however, its efficacy and safety are still unclear. The purpose of this meta-analysis was to evaluate the clinical efficacy and safety of TMPs combined with chemotherapy for the treatment of APC. Methods: A systematic search of eight electronic databases for randomized controlled trials (RCTs) was conducted from inception to October 15, 2021. Tumor response was identified as primary outcome, whereas quality of life (QoL), cancer biomarkers, and adverse drug reactions (ADRs) were identified as secondary outcomes. Quality of the evidence for each outcome was evaluated by GRADE profiler. Results: In total, 31 RCTs involving 1,989 individuals were included. This meta-analysis showed that TMPs combined with chemotherapy significantly improved the objective response rate (ORR) (RR=1.64, 95% CI [1.43 to 1.88], p <0.00001), disease control rate (DCR) (RR=1.29, 95% CI [1.21 to 1.38], p <0.00001), and QoL (continuous data: SMD=0.81, 95% CI [0.44 to 1.18], p <0.0001, dichotomous data: RR=1.44, 95% CI [1.22 to 1.70], p<0.0001), compared to those with chemotherapy alone. In addition, the combined treatment group also had lower levels of CA19-9 (SMD=-0.46, 95% CI [-0.90 to -0.02], p=0.04) and CEA (SMD=-0.55, 95% CI [-0.93 to -0.17], p=0.004). Moreover, TMPs reduced the ADRs during chemotherapy. Conclusion: This systematic review suggests that TMPs combined with chemotherapy might be a potential option to enhance therapeutic effects and reduce ADRs during the treatment of APC. However, more high-quality randomized controlled trials with more participants are needed. PROSPERO Number: CRD42021264938.